Food Logistics Quality: Minimize Damage to Fresh Fruit Shipping in Covid-19 Era - Vina Dwiyanti; Galuh Chisyti Nur Fadhilah; Indira Shaffiyah; Devanka Chelina; Erning Ertami Anton (Journal of Logistics and Supply Chain, 2022)
Food needs are the primary needs needed by all people in the world. Commodity food needs of fruits are needed by considering their quality. During the current Covid-19 pandemic, the demand for food delivery needs has greatly increased. The problem arises when the quality of the fruit is not suitable, it is damaged during delivery. This article aims to capture the quality of the fruit and how to minimize the damage in shipping. The method used in this study is a literature review using the source of scientific articles published in the last 10 years (2011-2021). The results of this study indicate that temperature, storage are the main factors in fruit delivery. In addition, in minimizing damage to fresh fruit in shipping, the use of a GPS-based temperature sensor is very good in maintaining the temperature during delivery as well as accurate information in real-time.